J. E. Shields correspondence - Shields, J. E.
ALS (Quartermaster's Dept., Cape Girardeau, Mo.) written by Shields to Col. J. B. Plummer concerning remuneration for the army's use of the privately owned steamer Luella.
Army officer.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Plummer, J. B. -- -1862 -- Correspondence; Luella (Steamer); United States. -- Army. -- Quartermaster Corps; Cape Girardeau (Mo.) -- History; Missouri -- History -- Civil War, 1861-1865.; United States -- History -- Civil War, 1861-1865.; Army officers